Advances in Controlled Meteorological (CMET) Balloon Systems - Voss, Paul B. (AIAA Balloon Systems Conference, 2009)
Over the past five years, small altitude-controlled balloons have been developed for atmospheric research and deployed in several major field campaigns. These Controlled Meteorological (CMET) balloons have been operated at altitudes from sea level to 18,000 feet, at latitudes from 18 to 80 degrees north, and for periods of up to five days. CMET balloons are now sufficiently simple to prepare and launch that they are being mailed to scientific collaborators oversees and operated remotely via satellite, greatly reducing the cost of making in situ atmospheric measurements. The balloon payload has been redesigned around a novel eight-parallel-processor microcontroller that enables exceptional flexibility and control with appreciable reductions in power consumption and weight. Miniature chemical sensors (carbon dioxide and sulfur dioxide) are now being used for quantifying contaminants and locating atmospheric layers. These new capabilities are being combined with near-real-time data processing, visualization, and control to enable CMET balloons to follow contaminant plumes in three-dimensional space, make repeated profile observations of mixing and dispersion, and report up-to-the minute position information to aviation safety officials. Successes and failures during recent campaigns in Mexico City, Hawaii, and the Arctic are discussed. Advances in balloon design and operations are described in the context of past flights and potential future applications.